Being Malay in Indonesia : Histories, Hopes and Citizenship in the Riau Archipelago - Long, Nicholas J. (Southeast Asia publications series., 2013)
The people of Indonesia's Riau Archipelago had long resented "colonial" control by Mainland Sumatra. In 1999, when the post-authoritarian state committed to democracy and local autonomy, they saw their chance to lobby for the region to be returned to its "native" Malays. In 2004, the islands officially became Riau Islands Province. This book explores what happened next. Living in a new province created "for Malays" forced Riau Islanders to engage with thorny questions over what it meant to be Malay and how to achieve the official goal of becoming globally competitive "human resources". - - Putting nuanced ethnographic observations of life in the islands into a provocative dialogue with theorists ranging from iek to Sartre, this impressive study explores the issue of Malay ethnicity in the ethnically diverse town of Tanjung Pinang (province of Riau), an area that straddles the cultural divide between contemporary Indonesia, Malaysia and Singapore. It explains how feelings of unsettledness and doubt came to permeate the province as a result of its very creation. Offering fresh perspectives on commerce, spirit beliefs, education and culture, Being Malay in Indonesia challenges much of the received wisdom in the anthropology of Southeast Asia and makes a powerful case for the importance of feelings, sentiments and affect in studies of local development and political change.